X-ray powder diffraction data for three red azo pigments: sodium, barium, and ammonium lithol salts. Issue 3 (29th June 2017) - Rafalska-Łasocha, Alicja; Grzesiak-Nowak, Marta; Goszczycki, Piotr; Ostrowska, Katarzyna; Łasocha, Wiesław
Abstract : Lithol reds belong to the group of azo pigments, which were popular artists' colouring materials in the first half of the twentieth century. These pigments were also used in many branches of industry. Here, we report X-ray powder diffraction data, unit-cell parameters, and space groups for three compounds from this group: sodium (E)-2-((2-hydroxynaphthalen-1-yl)diazenyl)naphthalene-1-sulphonate monohydrate (Na lithol red), monoclinic, space group C 2/c, with cell parameters a = 33.343(7), b = 6.667(2), c = 16.397(4) Å, β = 90.83°, V = 3644.51 Å 3, Z = 8; barium (E)-2-[(2-hydroxynaphthalen-1-yl)diazenyl]naphthalene-1-sulphonate trihydrate (Ba lithol red), monoclinic, space group P 21/ m, with cell parameters a = 17.758(9), b = 6.209(4), c = 16.857(8) Å, β = 92.07°, V = 1857.39 Å 3, Z = 2; and ammonium (E)-2-[(2-hydroxynaphthalen-1-yl)diazenyl]naphthalene-1-sulphonate monohydrate (NH4 lithol red), monoclinic, space group P 2/ c, with cell parameters a = 17.721(5), b = 6.428(3), c = 16.911(5) Å, β = 100.31(3)°, V = 1895.31 Å 3, and Z = 4. In the first and third cases we synthesised the pigments in their monohydrate form, performed X-ray powder diffraction measurements, and indexed all of the obtained diffraction maxima. In the case of the barium compound, despite many efforts in the course of the synthesis procedure, the powder diffraction patterns of the obtained samples were not of the best quality. Nevertheless, we indexed the best one and found a reliable space group and cell parameters.